Pengaruh fungisida asam fosfit, dimetomorf, dan metalaksil terhadap perkecambahan konidia Peronosclerospora maydis dan intensitas penyakit bulai jagung - Ginting, Cipta; Fauzia, Dita Nur; Swibawa, I Gede; Prasetyo, Joko (Universitas Lampung, 2025)
Downy mildew is one of the main diseases in maize which can reduce production. The objectives of this study were to determine the effect of phosphorous acid, dimetomorph, and metalaxyl fungicides on the germination and tube length of Peronosclerospora maydis conidia and the effect of phosphorous acid, dimetomorph, and metalaxyl fungicide treatment on conidia on the intensity of downy mildew in plants inoculated with these conidia. This study consisted of two tests, i.e., in vitro tests (effect on conidia germination and tube length) and in vivo tests (effect on downy mildew intensity). In both tests, a randomized block design (RBD) was used with four treatments and six replications. The results showed that phosphorous acid and dimethomorph fungicides inhibitted germination and reduced the length of conidia sprout tubes and suppressed downy mildew intensity. Meanwhile, metalaxyl fungicide was not effective in suppressing germination and conidia tube length and the intensity of downy mildew.